Morphoagronomic characterization of accessions of Triticum aestivum L. - Velasco-Laiton, Inés Yurany; Sana-Pulido, William Arnulfo; Morillo Coronado, Ana Cruz; Morillo-Coronado, Yacenia (Revista de Ciencias Agrícolas, 2022)
Wheat is one of the most economically important cereals for the Department of Boyacá; however, the cultivated area sees low yields, phytosanitary problems, and a lack of genetic materials with desirable agronomic characteristics. The present study aimed to morphoagronomically characterize 49 accessions from the FENALCE germplasm bank using morphological and yield descriptors and multivariate and cluster analyses. The variables auricle color, edge shape, precocity, growth habit, grain size and serosity showed little genetic variability, while the number of tillers per plant, number of spikelets per spike and glume color showed high genetic variability. The principal component analysis, based on the correlation matrix, showed that the first four principal components (PC) explained 71% of the total variation observed in the characterized accessions. The cluster analysis formed three groups according to the evaluated morphological characteristics, with group three containing the accessions with the best agronomic characteristics. None of the evaluated accessions had rust damage. Around 15 wheat accessions had good agronomic performance under the conditions of this study, which should be used in future genetic improvement programs aimed at identifying elite materials in the Department of Boyacá.